Elogio a "los servidores de la Palabra" (Lc 1,2) * - Galli, Carlos María (Teología, 2022)
* C. M. Ga l l i , "Prefacio. Elogio a "los servidores de la Palabra" (Lc 1,2), en: V. M. Fe r n á n d e z ; C. M. Ga l l i (eds.), "Testigos y servidores de la Palabra” (Lc 1,2). Homenaje a Luis Heriberto Rivas, Buenos Aires, San Benito, 2008, 7-16